SKRINING SELULASE DARI TANAH HUTAN MANGROVE PANTAI SUWUNG BALI - Wirajana, I Nengah; Ratnayani, Ketut; Asih Yuliana, Darma (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 2 Juli 2012, 2013)
Mangrove soil has high biodiversity and well known as potential location for enzymes exploration. The aim of direct screening for cellulase of mangrove soil is to find out the cellulase activity from mangrove soil. Mangrove soils were collected from three different locations labelled as A (8 o 43’38.20”SL), B (8 o 43’46,18”SL), and C (8 o 43’37,38”SL). The screening was conducted by Filter Paper Assay and Carboxymethyl Cellulose Assay methods. The results showed that cellulase activities can be measured directly from mangrove soil samples of Suwung Beach-Bali. The highest cellulase activities were 0,866 U/g soil by Filter Paper Assay and4,176 ± 0,630 U/g soil by Carboxymethyl Cellulose Assay , given by soil samples C.
Keywords: Cellulase, mangrove forest soil, Filter Paper Assay, Carboxymethyl Cellulose Assay.